An Extensive Analysis of Exercise Therapy as A Fall Prevention Measure For Older Individuals: Review (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
Genomics, decisions about our lives, and persistent illnesses are just a few of the various variables that interact during the complicated aging process and affect how we age. Aging reduces various physiological capacities, such as mobility, neuronal collaboration, strength of the muscles, and endurance, all of which degrade the ability to compete. It can also lead to a fall. Half of all injury deaths resulting from falls among seniors 65 and older occur in their homes. So, if we can prevent the fall, we can spare the victim from the resulting harm.